IMPLEMENTATION OF GUIDED INQUIRY LEARNING WITH SOCIO-SCIENTIFIC ISSUES CONTEXT TO STUDENTS' CRITICAL THINKING SKILLS ON BUFFER SOLUTION MATERIAL - Afifah, Sabrina Aulia; Sulistina, Oktavia; Setyowati, Istri (Universitas Negeri Surabaya, 2025)
This study aims to determine the effect of the application of guided inquiry learning model with Socio-Scientific Issues (SSI) context on students' critical thinking skills on buffer solution material. This study used a pre-experiment design type one group Pre-Test Post-Test with the subject of 30 students of class XI MIPA 6 SMA Laboratorium UM Malang. The measurement instrument was a reasoned multiple choice test to measure students' critical thinking skills. Data were analyzed using normality test, homogeneity, N-Gain analysis, and Wilcoxon test. The results showed an increase in the average Post-Test score by 36.48 points from the Pre-Test. The N-Gain value showed an increase in the medium (56.67%), low (40.00%), and high (3.33%) categories. Guided Inquiry Learning syntax cinsisting of Problem Orientation, Problem Formulation, Hypothesis Formulation, Investigation, Data Analysis, and Conclusion Drawing proved effective in encouraging students’ critical thinking skills. SSI contexts such as betel nut phenomenon provide contextual stimulus that helps students to be able to connect chemistry concept with their daily life and also strengthens students’ analysis and reflection in chemistry learning The Wilcoxon test results produced a significance value of 0.000 (p < 0.05) which means there is a significant difference between the Pre-Test and Post-Test. GIL syntax consisting of problem orientation, problem formulation, hypothesis formulation, investigation, data analysis, and conclusion drawing proved effective in encouraging students' critical thinking skills. SSI contexts such as the betel nut phenomenon provide contextual stimulus that strengthens students' analysis and reflection in chemistry learning.